The identification and detection of a unique gene in Salmonella enterica subsp. enterica Weltevreden using PCR-based approach - Tan C.; Yuan Xin G.; Chiann Ying Y.; Ismail A.; Kia Kien P. (2024)
Indexed by SCOPUS